2000
DOI: 10.1055/s-2000-9999
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of patients with iron deficiency anemia after a close endoscopic examination of the upper and lower gastrointestinal tract

Abstract: Based on our data, the prognosis of IDA with negative endoscopy is favorable. The pathogenic role of Helicobacter pylori infection should be evaluated in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 0 publications
0
13
1
3
Order By: Relevance
“…In published studies, the mortality rates range from 7% to 39% with a high heterogeneity in mean follow-up which range from 18 to 72 months. [10][11][12][13] In our study, the mortality was 26% in the subgroup of unexplained IDA, which is probably higher than previous studies. This can be explained by the fact that our population was significantly older than that of other studies.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…In published studies, the mortality rates range from 7% to 39% with a high heterogeneity in mean follow-up which range from 18 to 72 months. [10][11][12][13] In our study, the mortality was 26% in the subgroup of unexplained IDA, which is probably higher than previous studies. This can be explained by the fact that our population was significantly older than that of other studies.…”
Section: Discussioncontrasting
confidence: 49%
“…8 Moreover, a curative treatment in relation to endoscopic findings was usually carried out without increase of early mortality. 8 These results have also been observed by Joosten et al 9 However, to date, few data are available concerning long-term follow-up of elderly patients explored for IDA in the subgroups of patients with unexplained IDA [10][11][12][13] and no data are available in the subgroups of patients with benign lesions or cancer treated curatively or palliatively.…”
Section: Methodsmentioning
confidence: 66%
“…Most follow-up studies of patients admitted with nonvariceal AUGIB have revealed that more than two-thirds of patients diagnosed with anaemia prior to discharge recovered from anaemia after a period of 2-144 months. [12][13][14][15] Recently, a retrospective study showed that more than 80% of patients admitted to the hospital with nonvariceal AUGIB were anaemic at the time of discharge from a semi-intensive-care unit. However, only 16% of the anaemic patients received a recommendation to begin oral iron supplementation by their surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…However, we were not able to detect any pathological lesion by radiologic examination in our patients. Previously, it has been shown that the prognosis of IDA in elderly patients who had negative gastrointestinal evaluation is favorable [22]. …”
Section: Discussionmentioning
confidence: 99%